Developing Students’ Language Awareness through Discovery Learning in English Language Teaching - Meiva Mutia Rahmi; Rita Erlinda (Universitas Negeri Padang, 2014)
Language acquisition has strong relation with language awareness which is very important in order to be a good language user, because it is a person’s sensitivity to and conscious awareness of language and its role in human life. It deals with explicit knowledge about language, and conscious perception and sensitivity in language learning, language teaching and language use. Language awareness includes the knowledge about language, a conscious understanding of how languages work, of how people learn them and use them. In English language teaching the use of language in classroom interaction is not only for communication, it is also used to deliver norm through language, meanwhile in Indonesia, most of student is multilingual where they have already acquired languages, including their mother tongue and their national language, the students’ awareness in learning foreign language such English is a crucial issue to be considered. One of technique that can be used to develop students’ language awareness is through discovery learning. It is an inquiry-based theory which encourages students to be active agents in their own learning process, including in language learning. Discovery learning in English language teaching allows the students to work on language by having a role in their own learning and developing their activity through the language. So, this paper aims to give an overview how to apply discovery learning in English language teaching to develop student language awareness.